Political Empowerment Support to Ecotourism Development: A Study the Indigenous Tribal Populations in India - Remya Kumar; Manoj Edwar; Babu George (Centre For Tourism Planning and Development, 2021)
This research was framed as an attempt to empirically retest the assumed relationship between political empowerment and resident support for ecotourism, with perceived benefits and perceived costs as mediating variables. The study is analytical-descriptive in nature and followed a cross-sectional survey design. The survey participants included the local inhabitants of the ecotourism zones of three protected areas in India. On the basis of a review of the literature pertaining to community-based tourism, an initial research instrument was developed. This questionnaire included items to measure political empowerment, perceived benefits of ecotourism, perceived costs of ecotourism, and support for sustainable tourism development, that were adopted from previous studies. The results derived from the Structural Equation Modeling of the data gathered by us, quite contrary to indications in the literature, suggest that political empowerment critically diminishes destination local community support for ecotourism development. Even though the extant literature generally indicates that empowerment is central to community-based tourism, it appears that, under certain conditions, empowered community members might skip tourism and pursue alternate economic opportunities.